The coordinated development of Beijing-Tianjing-Hebei urban research - Yongwu, Zheng; chongcong, zhang; Jian, Zhang (Advances in Social Sciences Research Journal, 2015)
The Beijing-Tianjing-Hebei in China plays a decisive role in economic and social development. The coordinated development of urbanization of the Beijing-Tianjing-Hebei region, will greatly improve the level of regional urbanization, promote regional economic development, promote urbanization and economic development of Bohai rim region. Adhere to the principle of complementary advantages and win-win cooperation, establish the coordinated development of Beijing-Tianjing-Hebei urban mechanism, overall planning of Beijing-Tianjing-Hebei urbanization. In order to improve the urbanization level as the goal of the Beijing-Tianjing-Hebei region, optimization of regional industry layout, strengthen ecological environment comprehensive treatment, and strengthening regional urban construction coordination, coordination and ecological environment protection coordination of industrial development, realize the coordinated development of Beijing-Tianjing-Hebei urbanization.